TEACHING SOCIAL HUMANITARIAN SUBJECTS IN UNIVERSITY: NAVIGATING COMPLEXITIES AND CONTROVERSIES IN THE CLASSROOM TO EMPOWER STUDENTS - Khakimov , Nazar; Amridinova , Dilrabo; Kurbanova, Sevara (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article explores the complexities and controversies involved in teaching social humanitarian subjects in university, and provides strategies for educators to navigate these challenges in a way that empowers students. The article emphasizes the importance of creating a respectful and inclusive classroom environment, providing diverse perspectives, and addressing controversial topics with empathy and sensitivity. By empowering students to engage with social and humanitarian issues in meaningful ways, educators have the potential to inspire the next generation of global citizens and social justice advocates.